The Influence of Transcranial Alternating Current Stimulation on the Excitability of the Unstimulated Contralateral Primary Motor Cortex - Erik W. Wilkins; Richard J. Young; Ryder Davidson; Reese Krider; George Alhwayek; Jonathan A. Park; Armaan C. Parikh; Zachary A. Riley; Brach Poston (Brain Sciences)
Objectives: Transcranial alternating current stimulation (tACS) can enhance primary motor cortex (M1) excitability and improve motor skill when delivered unilaterally to the dominant hemisphere. However, the impact of tACS on contralateral M1 excitability both during and after application has not been studied. The purpose of this study was to examine the effects of tACS delivered to the dominant left M1 on the excitability of the unstimulated contralateral non-dominant right M1. Methods: This study implemented a double-blind, randomized, SHAM-controlled, within-subjects, crossover experimental design. Eighteen young adults completed a tACS condition and a SHAM condition on two different days in counterbalanced order with a week washout period between days. Transcranial magnetic stimulation (TMS) was utilized to assess excitability of the contralateral right M1 while tACS was delivered to the left M1. TMS was administered in five test blocks (termed Pre, D5, D10, D15, and Post) relative to a 20 min application of tACS (70 Hz, 1 mA current strength). The Pre and Post TMS test blocks were conducted before and immediately after tACS was applied to the left M1, whereas the TMS test blocks performed during tACS were completed at time points starting at the 5, 10, and 15 min marks of the 20 min stimulation period. The primary dependent variable was the 1 mV motor evoked potential (MEP) amplitude. MEP data were analyzed with a 2 condition (tACS, SHAM) × 5 test (Pre, D5, D10, D15, Post) within-subjects ANOVA. Results: The main effect for condition (p = 0.704) and condition × test interaction (p = 0.349) were both non-statistically significant. There was a significant main effect for test (p = 0.003); however, post hoc analysis indicated that none of the pairwise comparisons were statistically significant. Conclusions: Overall, the findings indicate that tACS applied to the left M1 does not significantly modulate contralateral right M1 excitability during or immediately after stimulation, at least when utilizing the present tACS parameters.